The Effect of Nano-Scale Topography on Keratinocyte Phenotype and Wound Healing Following Burn Injury - Parkinson, Leigh G. (Mary Ann Liebert, Inc., 2012)
Topographic modulation of tissue response is an important consideration in the design and manufacture of a biomaterial. In developing new tissue therapies for skin, all levels of architecture, including the nanoscale need to be considered. Here we show that keratinocyte phenotype is affected by nanoscale changes in topography with cell morphology, proliferation, and migration influenced by the pore size in anodic aluminum oxide membranes. A membrane with a pore size of 300 nm, which enhanced cell phenotype in vitro, was used as a dressing to cover a partial thickness burn injury in the pig. Wounds dressed with the membrane showed evidence of advanced healing with significantly less organizing granulation tissue and more mature epidermal layers than control wounds dressed with a standard burns dressing. The results demonstrate the importance of nanoscale topography in modulating keratinocyte phenotype and skin wound healing.